Investigation of The Effect Hullvane and Bow Foil on Flat-Hull Ship Using CFD Approach - Andi Trimulyono; Wahyu Ananda; Kiryanto Kiryanto; Ari Wibawa Budi Santosa (International Journal of Marine Engineering Innovation and Research, 2023)
The flat-hull ship design is an innovative concept that saves costs and speed-up the fabrication of the ship. Even though the flat-hull ship was hydrodynamically inefficient, some shipowners probably experienced an issue with its unusual shape and disadvantages where drag is greater than that of conventional ships. This paper aimed to improve the design of a flat-hull vessel using hull vane and bow foil to reduce ship resistance. The asymmetric foil NACA 4412 and 0012 were used for the hull vane. For bow foil, only NACA 4412 is used. In addition, the angle of the strut of the hull vane was varied to find out the effect to ship resistance. This study was performed in a numerical approach using computational fluid dynamics (CFD). The mesh-based CFD with RANSE solver was used in this study, and numerical analysis will be conducted to determine ship resistance of flat-hull ships with hull-vane and bow foil. It was found that the effectiveness of hull vanes on ships failed to improve resistance for flat-hulled vessels. Because of the addition of the WSA on the ship, the total resistance of the ship increases following the installation of the hull vane. As an alternative, using bow foil can reduce ship resistance at Fn 0.44 and 0.59 by 10% and 24%, respectively.